A COMPARATIVE STUDY OF STUDENT"™S MATHEMATICAL REPRESENTATION ABILITY USING JIGSAW VS STUDENT FACILITATOR AND EXPLAINING - Sari, Merisa Ammelia; Dasari, Dadan (Jurnal Pendidikan Matematika dan IPA, 2025)
One of the most important skills in mathematics is mathematical representation, which is the ability to develop and represent mathematical concepts in symbols. However, most students have difficulties in developing mathematical ideas in this form. This research aims to improve students"™ mathematical representation ability by using the jigsaw learning model and the student facilitator and explaining learning model. The two learning models are compared to see which is more effective in increasing students"™ mathematical representation skills. This research is a quasi-experimental method performed at a senior high school in Deli Serdang Regency, North Sumatra Province. A random sampling technique was used and two groups were compared, with the experimental group-1 treated with the jigsaw learning model and the experimental group-2 with the student facilitator and explaining learning model. Data collection techniques include interviews, observation, and tests as the instruments. An Independent t-test sample was used in data processing and analysis. The research findings identified that the students of the jigsaw learning model have a significantly higher mathematical representation ability compared to those of the facilitator and explaining learning model. Based on this finding, it is concluded that the jigsaw learning model is more effective in developing and representing mathematical ideas in symbols.